2020
DOI: 10.1007/s12182-020-00426-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of the porphyrins and demulsifiers in the aggregation process of asphaltenes at water/oil interfaces under desalting conditions: a molecular dynamics study

Abstract: Breaking water-in-oil emulsions during the refining of crude oils is an important step before any upgrading process is started. Asphaltene molecules are incriminated as playing an important role in this phenomenon. Unraveling the mechanisms behind the affinity between them and water is a key step to understand how to break these emulsions more easily and require lower amounts of demulsifiers. Choosing which demulsifier molecule(s) to use is also primordial, but to do so rationally, one needs to know which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 73 publications
0
6
0
1
Order By: Relevance
“…The composition of the vanadyl porphyrins eluting in the most aggregated region (leftmost plot) spans the largest carbon number range. As aggregation lessens, the carbon number range narrows and the average H/C ratio decreases to almost 1.0, corresponding to species with very little alkylation on the core, tetrapyrrolic porphyrin structure. ,, Increased aggregation correlated to decreased aromaticity and greater abundance of more aliphatic species for all of the heteroatom classes observed. Figure confirms that correlation for three of the most abundant heteroatom classes in the whole asphaltenes.…”
Section: Results and Discussionmentioning
confidence: 95%
“…The composition of the vanadyl porphyrins eluting in the most aggregated region (leftmost plot) spans the largest carbon number range. As aggregation lessens, the carbon number range narrows and the average H/C ratio decreases to almost 1.0, corresponding to species with very little alkylation on the core, tetrapyrrolic porphyrin structure. ,, Increased aggregation correlated to decreased aromaticity and greater abundance of more aliphatic species for all of the heteroatom classes observed. Figure confirms that correlation for three of the most abundant heteroatom classes in the whole asphaltenes.…”
Section: Results and Discussionmentioning
confidence: 95%
“…The π-stacking interactions are not strong enough to explain why porphyrins are commonly found within asphaltene aggregates [214]. The formation and stabilization of asphaltene nanoaggregates are dependent on the size of the conjugated core and the eventual presence of polar groups capable of forming H bonds [212,215]. Vanadyl porphyrins, even without polar lateral chains, can interact considerably strongly with asphaltene molecules via the formation of H bonds from the central O atom [194,213].…”
Section: Role Of Heteroatoms and Metals In Asphaltene Aggregationmentioning
confidence: 99%
“…Moreover, calculations show that asphaltene–asphaltene interaction energies are larger than asphaltene–porphyrin interaction energies, which support the idea that trapped compounds and resins preferentially bond to porphyrins rather than asphaltenes in large aggregates. , These conclusions were supported by molecular dynamics calculations that take into account solvent effects, asphaltene diversity, and thermodynamics conditions and concluded that metalloporphyrins do not directly affect asphaltene–asphaltene interactions. ,,, However, polar lateral chains on porphyrin core structures leads to hydrogen bond interactions with both asphaltenes and water, causing reinforcement of π-stacking interactions between asphaltenes. Therefore, the presence of metalloporphyrins may display an interfacial activity and, depending on the solvent, induces either a stronger precipitation in n -heptane or stabilizes aggregate at a water/oil interfaces. ,, …”
Section: Molecular Simulations and Computational Approachesmentioning
confidence: 70%